ANALISIS PENGARUH HARGA DAN E-SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (STUDI PADA ONLINE SHOP FUTNEEDSSTORE) - M. Hero Fariqo (2022)
This study aims to examine the effect of price and e-service quality on customer loyalty which is intervened by customer satisfaction at Futneedsstore Stores. The development of digital buying and selling transactions makes store managers continue to develop services and competitive product prices. Store managers need to get an overview of product prices and service quality to increase customer loyalty. This study uses intervention variables to explain the level of customer loyalty. The data collection technique in this study used purposive sampling with the number of respondents. The requirements for this research respondent are Futneedsstore customers who have shopped at least 2 times. The analytical test tool used is SmartPLS v.3.2.7 with the SEM (Structural Equation Modeling) analysis method. The results of this study indicate that price has a significant effect on customer satisfaction but does not have a significant effect on customer loyalty, e-service quality has a positive and significant effect on customer satisfaction and customer loyalty, and customer satisfaction is proven to mediate the effect of e-service quality on customer loyalty.